High dielectric constant polyaniline/epoxy composites via in situ polymerization for embedded capacitor applications - Lu, Jiongxin; Moon, Kyoung-Sik; Kim, Byung-Kook; Wong, C. P. (ELSEVIER SCI LTD, 2007)
Polyaniline (PANI)/epoxy composites with different polyaniline (PANI) contents were successfully developed by in situ polymerization of aniline salt protonated with camphorsulfonic acid within epoxy matrices and fully characterized. The influence of PANI loading levels on various properties was also explored. Dielectric and electrical properties of PANI/epoxy composites were studied for samples in parallel plate configuration. A PANI/epoxy composite prepared in this fashion reached a high dielectric constant close to 3000, a dielectric loss tangent less than 0.5 at room temperature and 10 kHz. The hardener type was also found as a critical parameter for the dielectric properties of PANI/epoxy composites. The distribution of the conductive element clusters within the polymer matrix was studied by SEM and correlated to the dielectric behavior of the composite films. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: ELECTRICAL-PROPERTIES; BEHAVIOR; MATRIX; RESIN